A Drug‐Delivery Vehicle Combining the Targeting and Thermal Ablation of HER2+ Breast‐Cancer Cells with Triggered Drug Release1. Issue 15 (11th March 2013) - You, Jin‐Oh; Guo, Peng; Auguste, Debra T.
<x xml:space="preserve">Abstract</x> Covering all three bases: Drug‐delivery vehicles that encapsulate doxorubicin (Dox) within a pH‐sensitive matrix embedded with gold nanoparticles were synthesized with Herceptin–poly(ethylene glycol) conjugates on the surface for the specific binding of cancer cells (see picture; NIR=near infrared). Cell targeting was combined with enhanced cytotoxicity through triggered drug release (at pH 5–6) and thermal ablation (a photothermal effect).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>